Socioeconomic environment and disparities in cancer survival for 19 solid tumor sites: An analysis of the French Network of Cancer Registries (FRANCIM) data. Issue 6 (3rd December 2018) - Tron, Laure; Belot, Aurélien; Fauvernier, Mathieu; Remontet, Laurent; Bossard, Nadine; Launay, Ludivine; Bryere, Joséphine; Monnereau, Alain; Dejardin, Olivier; Launoy, Guy; ,
Abstract : Social inequalities are concerning along the cancer continuum. In France, social gradient in health is particularly marked but little is known about social gradient in cancer survival. We aimed to investigate the influence of socioeconomic environment on cancer survival, for all cancers reported in the French Network of Cancer Registries. We analyzed 189, 657 solid tumors diagnosed between 2006 and 2009, recorded in 18 registries. The European Deprivation Index (EDI), an ecological index measuring relative poverty in small geographic areas, assessed social environment. The EDI was categorized into quintiles of the national distribution. One‐ and five‐year age‐standardized net survival (ASNS) were estimated for each solid tumor site and deprivation quintile, among men and among women. We found that 5‐year ASNS was lower among patients living in the most deprived areas compared to those living in the least deprived ones for 14/16 cancers among men and 16/18 cancers among women. The extent of cancer survival disparities according to deprivation varied substantially across the cancer sites. The reduction in ASNS between the least and the most deprived quintile reached 34% for liver cancer among men and 59% for bile duct cancer among women. For pancreas, stomach and esophagus cancer (among men), and ovary and stomach cancer (among women), deprivation gaps were larger at 1‐year than 5‐year survival. In conclusion, survival was worse in the most deprived areas for almost all cancers. Our results from population‐based cancer registries data highlight the need for implementing actions to reduce social inequalities in cancer survival in France. Abstract : What's new? Individual socioeconomic characteristics are known to be strong predictors of cancer survival worldwide. However, not only individual but also contextual and environmental factors might contribute to social inequalities in cancer survival. Using the French Network of Cancer Registries, here the authors show, for the first time in France, that cancer survival is lower for patients living in the most deprived areas compared to those living in the least deprived ones, for almost all solid tumors, with variable magnitudes across the cancer sites. The findings highlight the need for public health policies to reduce social inequalities in cancer survival in France.